Identifikasi dan Analisis Risiko K3 Menggunakan Metode Hiradc dan Jsa di Home Industry Marno Art - Samuel Ariel Hermawan; Brillian Nur Diansari; Garnet Filemon Waluyono (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Home Industry Marno Art Collection is a business in the field of fabric production and dyeing that still uses manual work processes so that it has various potential occupational hazards. This study aims to identify potential hazards, assess the level of risk, and determine risk control using the Hazard Identification, Risk Assessment and Determining Control (HIRADC) and Job Safety Analysis (JSA) methods. The study used a qualitative descriptive approach through observation, interviews, documentation, and literature studies. The results showed that the highest risk was found in chemical exposure in the dye mixing process with a risk value of 16 which is included in the high category. Recommended risk controls include the use of personal protective equipment, improved ventilation, preparation of SOPs, and OHS training. The application of the HIRADC and JSA methods is effective in identifying hazards and determining risk control priorities.